Techno-economic assessment of thorium power in Canada. (November 2015) - Graves, Brian; Wong, Alain; Mousavi, Kian; Canter, Christina; Kumar, Amit
Highlights: Costs of replacing uranium in Canada's nuclear reactors with thorium evaluated. Results show a thorium plant to be more financially lucrative than a uranium plant. Results were most sensitive to electricity price, then capital and decommissioning cost. Abatement cost analysis showed nuclear power offers cost savings over fossil fuels. Abstract: Thorium fission is a large yet relatively unexplored renewable energy source and could help feed increasing energy demands. An analysis was performed on the feasibility of replacing the uranium in Canada's nuclear reactors with thorium. Thorium only exists as a fertile isotope, and so an external fissile source such as 235 U, 233 U, or 239 Pu is required to stimulate the fission process. A uranium plant and a similar thorium-fuelled plant were compared over a 40 year operational life based on a comprehensive economic analysis. The results from the economic analysis were used to estimate the greenhouse gas (GHG) abatement cost compared to the coal and natural gas-based power. The economic analysis determined that a thorium plant is more financially lucrative in Canada than a uranium plant. An abatement cost assessment in relation to gas-fired and coal-fired power plants demonstrated that nuclear power offers a cost savings per tonne of CO2 equivalent greenhouse gas (GHG) when compared to both fossil fuel alternatives. From the values determined for a plant potentially fuelled on thorium, the abatement cost when compared to the coal-fired and gas-fired plants is −$10.4/tonne-CO2 eq and −$15.7/tonne-CO2 eq, respectively.